Important factors for the three-dimensional reconstruction of neuronal structures from serial ultrathin sections - Kubota, Yoshiyuki; Hatada, Sayuri; Kawaguchi, Yasuo (Frontiers in Neural Circuits, 2009)
Quantitative analysis of anatomical synaptic connectivity in microcircuits depends upon accurate 3-dimentional reconstructions of synaptic ultrastructure using electron microscopy of serial ultrathin sections. Here we address two pitfalls in current methodology that lead to inaccurate reconstructions and compromise conclusions drawn from the data. The first pitfall is inaccurate determination of ultrathin section thickness, which negatively affects the three-dimensional shape of reconstructions and therefore impairs quantitative measurement of synaptic structures. Secondly, current methodology significantly underestimates the number of synaptic junctions, with only two-thirds or less of genuine synaptic contacts being identified in dendrites that radiate within the plane of section. Here we propose a new methodology utilizing precise optical measurements of section thickness and successive observations of synaptic elements across serial ultrathin sections that corrects for these limitations to allow accurate 3-dimentional reconstruction of synaptic ultrastructure. We use this methodology to reveal that parvalbumin-expressing cortical interneurons have a much higher synaptic density than previously shown. This result suggests that this technique will be useful for re-examining synaptic connectivity of other cell types.